Glutamine Inhibition Reduces Iatrogenic Laryngotracheal Stenosis. (12th January 2021) - Tsai, Hsiu‐Wen; Lina, Ioan; Motz, Kevin M; Chung, Liam; Ding, Dacheng; Murphy, Michael K.; Feeley, Michael; Elisseeff, Jennifer H.; Hillel, Alexander T.
Abstract : Objective/Hypothesis: Glutamine inhibition has been demonstrated an antifibrotic effect in iatrogenic laryngotracheal stenosis (iLTS) scar fibroblasts in vitro. We hypothesize that broadly active glutamine antagonist, DON will reduce collagen formation and fibrosis‐associated gene expression in iLTS mice. Study Design: Prospective controlled animal study. Methods: iLTS in mice were induced by chemomechanical injury of the trachea using a bleomycin‐coated wire brush. PBS or DON (1.3 mg/kg) were administered by intraperitoneal injection ( i.p .) every other day. Laryngotracheal complexes were harvested at days 7 and 14 after the initiation of DON treatment for the measurement of lamina propria thickness, trichrome stain, immunofluorescence staining of collagen 1, and fibrosis‐associated gene expression. Results: The study demonstrated that DON treatment reduced lamina propria thickness ( P  = .025) and collagen formation in trichrome stain and immunofluorescence staining of collagen 1. In addition, DON decreased fibrosis‐associated gene expression in iLTS mice. At day 7, DON inhibited Col1a1 ( P  < .0001), Col3a1 ( P  = .0046), Col5a1 ( P  < .0001), and Tgfβ ( P  = .023) expression. At day 14, DON reduced Co1a1 ( P =  .0076) and Tgfβ ( P =  .023) expression. Conclusions: Broadly active glutamine antagonist, DON, significantly reduces fibrosis in iLTS mice. These results suggest that the concept of glutamine inhibition may be a therapeutic option to reduce fibrosis in the laryngotracheal stenosis. Level of Evidence: N/A Laryngoscope, 131:E2125–E2130, 2021